The Effect of Raw Material Quality on Donut Texture and Taste: A Case Study of a Donut Micro, Small, and Medium Enterprise (MSME) in Naga Timbul Village - Ikwan Lubis; A M Hatuaon Sihite; Nurin Natiqoh Lubis; Maringan Sianturi (Devitara Innovations, 2026)
Raw material quality is one of the key factors determining the quality of food products, particularly in the bakery industry. The donut-producing Micro, Small, and Medium Enterprise (MSME) in Naga Timbul Village faces several challenges in maintaining product consistency due to variations in the quality of raw materials used during the production process. This study aims to analyze the influence of raw material quality on the texture and taste of donuts produced by the MSME in Naga Timbul Village, Tanjung Morawa District, Deli Serdang Regency. This research employed a qualitative approach using a descriptive method. Data were collected through direct observations, semi-structured interviews with the business owner and employees, and documentation of the production process. Data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings indicate that the quality of raw materials, particularly wheat flour, yeast, sugar, eggs, margarine, and cooking oil, significantly influences the texture and taste of the donuts. The use of high-quality raw materials produces donuts with a softer texture, better elasticity, more appealing aroma, and superior flavor preferred by consumers. In addition, appropriate fermentation and frying processes contribute to maintaining consistent product quality. The study concludes that effective raw material quality control and proper production practices are essential for improving product quality, increasing customer satisfaction, and enhancing the competitiveness of MSMEs. The findings are expected to provide practical recommendations for MSME owners in implementing sustainable quality control practices to improve product performance and business competitiveness.